Application of OCT in the research of amblyopic fundus - Yuan Ma (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
Amblyopia is a common eye disease in children. If not corrected and treated in time, it will cause irreversible damage to children's vision, resulting in loss of vision in one or both eyes. The pathogenesis of amblyopia is complex, and the specific pathogenesis is not clear at present, mainly focusing on the central theory and peripheral theory. Traditionally, there was no obvious organic change in the fundus of amblyopia patients. In recent years, optical coherence tomography(OCT)technology has developed rapidly. As a convenient and intuitive ophthalmic examination method, OCT has been increasingly used in retinal examination of amblyopia patients due to its advantages of safety, non-invasive, non-contact and rapid and clear. The abnormal anatomy structures of the amblyopia patients in fundus structure are also gradually been found. Providing some evidence and basis for peripheral theory of pathogenesis of amblyopia, amblyopia examine, postoperative evaluation and prognosis. In this article, the applications of OCT in retinal thickness, choroid thickness and vessel density are reviewed.